Requirements Documentation for Manufacturing Systems: Template and Management Tool - Ahmadi, Mahnaz (My University, 2006)
The experience shows that any shortcoming in defining the requirements for computer based systems imperils the deliverables of all the subsequent stages of their development. This importance is undeniable when dealing with manufacturing software-systems due to their significant role in all spheres of human life. These systems have very stringent non-functional requirements such as accuracy and real-time constraints. The development of manufacturing software-systems is very challenging and requires special caution, since any mistake might have broad impact on very expensive work-pieces or might lead to a machining accident with irreparable effects. The success of their development depends largely on the quality of their Software Requirements Specification Document (SRSD).
We propose a new requirements template specifically designed for manufacturing systems. The template is structured to reflect their characteristics including multi-constraints and multi-disciplinary problems, multi-stage processes, multi-tasking, dynamic behavior, evolutionary nature, time-varying physical characteristics, and the usage of complex scientific models. A complementary usage of goal-driven, viewpoint oriented, and scenario-based approach is adopted for structuring the template content. To provide a high quality SRSD, the template is designed to enhance unambiguity, consistency, completeness, precision, non-redundancy, and good organization of the requirements document as well as other criteria including breadth of applicability and methodology independence.
An automated tool for requirements management according to the proposed template has been designed and implemented. The requirements management tool provides relatively secure and easy-to-use capabilities for the documentation and the retrieval of the requirements. It accelerates capturing the requirements, improves system quality by enhancing the reduction of requirements errors, and helps in establishing a common understanding between the system builders and the stakeholders. In addition to a user friendly environment for changing the information, we developed a powerful dynamic report generator that can be configured by the user and that provides a simple way for retrieving the requirements and formatting them.
Both the template and the tool have been validated using the requirements for a Tool Trajectory Planning for High Speed Machining system developed at the Aerospace Manufacturing Technology Centre, Institute for Aerospace Research (Montreal).
Keywords: manufacturing systems, template, management tool, requirements, documentation, SRSD